Immunohistochemical expressionof sodium-dependent glucose transporter - 2 (SGLT-2) in clear cell renal carcinoma: possible prognostic implications - Kobayashi,Minoru (2019)
ABSTRACT Purpose: Glucose is a major energy resource for tumor cell survival and growth, and its influx into cells is mainly carried out by facilitative glucose transporters (GLUTs). Sodium - dependent glucose transporters (SGLTs) have been highlighted as playing important roles in diabetic treatment. However, their potential roles in cancer remain unclear. We examined expression patterns of SGLTs in tumor tissues together with conventional pathological variables to determine prognostic significance in patients with renal cell carcinoma (RCC). Materials and Methods: Nephrectomy specimens were obtained from 68 patients. GLUT - 1, - 2 and SGLT - 1, - 2 expression in tumor and adjacent normal tissues were analyzed by immunohistochemical staining, and intensity was quantified using an image analyzer. Results: The four glucose transporters evaluated were broadly distributed in tumor tissues as well as throughout the normal parenchyma. There was no significant correlation between transporter expression and conventional pathological variables. However, increased SGLT - 2 expression was significantly associated with shorter overall survival (p < 0.01), regardless of metastatic status. Conclusions: We propose possible prognostic significance of SGLT - 2 expression in human RCC. Given that glucose is a major energy resource for tumor cells and that glucose transport is largely mediated by SGLT, SGLT - 2 may serve as a possible therapeutic target in RCC.